OPTIMIZATION OF TURNOVER THROUGH IMPROVING THE QUALITY AND PRODUCTIVITY OF PROCESSED GAR-DERIVATIVE PRODUCTS IN KWALA BEGUMIT VILLAGE, STABAT DISTRICT - Yasmin Chairunisa Muchtar; Adika Fajar Putra; Jane Melita Keliat (RADJA PUBLIKA, 2024)
Agarwood is a tree from the genus Aquaria which generally grows in Southeast Asia and South Asia. The Cagar Jaga Nusantara Cooperative is a cooperative that works to promote and preserve agarwood plants as a commodity that produces a positive impact on humans. Apart from empowering this cooperative, this cooperative also directly participates in the processing of agarwood plants, processing various types of derivative products made from agarwood, such as agarwood soap, coffee, agarwood tea, agarwood buhur (incense), agarwood sapwood and distilled water. Activities that have been carried out include training, education and teaching to the team to improve the quality and productivity of 'Herbal Agarwood Tea'. The potential for developing other processed agarwood products, such as soap and distilled water, will be studied further. This has the opportunity to increase the amount of money generated. Businesses will become more creative with this training, and it can open up jobs for the local community. Therefore, it is hoped that business people will become pioneers of Agarwood Products in North Sumatra.